Risk regulation and administrative constitutionalism - Fisher, Elizabeth (Elizabeth Charlotte) (Hart, 2007)
The regulation of environmental and public health risks is a controversial area of government activity. This book studies the public law dimension of these controversies, particularly the interrelationship between risk regulation, public law and theories of legitimate administrative governance.